Temporal trajectories of enacted complexity in creative project teams - GOH, Kenneth T. (Institutional Knowledge at Singapore Management University, 2018)
With technologies to capture fine-grained measures of behavior now more ubiquitous, organizational researchers are now able to consider networks of actions performed by multiple actors as a unit of analysis. We apply the action network construct as a measure of enacted complexity. Because previous conceptualizations of complexity viewed the construct as a descriptive organizational property, capturing this property over time was a non-issue. But given the emergent nature of enacted complexity, questions about how complexity unfolds over time become meaningful. This paper thus examines how enacted complexity unfolds over time by investigating the temporal trajectory of actors and actions. We present our findings from an analysis of 11,023 task sequences of four videogame development projects with qualitative data collected over two years.